New prognostic index to detect the severity of asthma automatically using signal processing techniques of capnogram - Mohsen Kazemi, 1982-, author; Malarvili Bala Krishnan, supervisor; Fakulti Biosains dan Kejuruteraan Perubatan (2013)
Thesis (Ph.D (Kejuruteraan Bioperubatan)) - Universiti Teknologi Malaysia, 2013